The Crush of Life’s Passion: Interiority in Michel Henry as a Possibility for the Experience of God - Simon Cunningham (Religions)
The question of whether God can be given in first-hand experience is debated in the secondary literature of Michel Henry. Articulating the history and structure of interiority more deeply provides a more precise conceptualization of his interiority to emerge and thus settle the question, namely that Henry’s thought contains both a dualism and duality. Within his dualism, Henry’s interior appearing is foundational, and has no capacity to reconcile with the world’s appearing that asserts exteriority as a foundation of what is given. Yet an interior/exterior duality emerges within Henry’s foundational interiority. Experiences of things like chairs are exteriorly given in life, while experiences of affectivity like gratitude are interiorly given in life. Since interior experiences are unified with our life and are our life, they lack any phenomenological distance that reduce God to finitude. Thus interiority, when both the foundation and the experience, establishes both a possibility for a first-hand experience of God and a glimpse into God’s experience of Godself. The article closes by showing how Henry suggests a name for God when given in first-hand experience: the Holy Spirit.